2021
DOI: 10.1177/00368504211011339
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and profile of acute intoxication among adult population in Najran, Saudi Arabia: A retrospective study

Abstract: Acute poisoning is considered one of the most important medical emergencies, resulting in severe morbidity and mortality, and is an economic burden on governments. This study aimed to determine the extent of acute adult intoxication among the population located in the Najran area, Saudi Arabia, over the last 3 years (from January 2017 to December 2019). The study is a hospital-based retrospective observational study. The data of all acutely intoxicated adult patients were collected from patients’ files of King… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 56 publications
0
14
1
Order By: Relevance
“…The findings of the study are consistent with another study that reported that approximately 10.6% of patients in Najran, Saudi Arabia were under the influence of heavy alcohol intake. However, unlike the present study’s results, in which one death was reported, the prior study demonstrated good patient outcomes [ 20 ]. A study conducted at Al-Amal Hospital in Jeddah noted that 16.1% of patients were consuming and abusing alcohol [ 21 ].…”
Section: Discussioncontrasting
confidence: 94%
“…The findings of the study are consistent with another study that reported that approximately 10.6% of patients in Najran, Saudi Arabia were under the influence of heavy alcohol intake. However, unlike the present study’s results, in which one death was reported, the prior study demonstrated good patient outcomes [ 20 ]. A study conducted at Al-Amal Hospital in Jeddah noted that 16.1% of patients were consuming and abusing alcohol [ 21 ].…”
Section: Discussioncontrasting
confidence: 94%
“…All 30 articles included in this systematic review were observational studies (seven cohort studies and 23 cross-sectional studies). Of the 30 studies, 26 (86.66%) obtained their data from an administrative database and/or patient interviewing [3,[14][15][16][17][18][21][22][23][24]26,[28][29][30][31][32][34][35][36][37][38][39][40][41], two studies (6.66%) from a survey [33,42], and two studies (6.66%) did not specify the data source [19,27]. Most of the studies reported the outcomes over a short period.…”
Section: Methodological Characteristics Of Included Studiesmentioning
confidence: 99%
“…All articles were written in English and conducted in Saudi Arabia. Thirteen studies were from the Riyadh region [3,[14][15][16][17][18][19][20][21][22][23][24][25], nine were from the Makkah region [26][27][28][29][30][31][32][33][34], three studies were from the Eastern region [35][36][37], three studies were from the Qassim region [38][39][40], one study was from the Najran region [41], and one study covered entire Saudi Arabia [42]. In relation to the range of years of publication, the oldest article was from 2012, and the latest was from 2021.…”
Section: General Characteristics Of Included Studiesmentioning
confidence: 99%
“…We believe that the prevalence of drug overdose has increased in the past years, based on our observation, and it will continue to rise among our population, according to multiple research studies regarding drug overdose in Saudi Arabia [ 4 , 6 , 7 ]. In addition, there is quite a lack of updated studies about drug overdose in Saudi Arabia in general and Jeddah City specifically.…”
Section: Introductionmentioning
confidence: 94%
“…In Saudi Arabia, drug overdose has been accountable for many intensive care unit (ICU) admissions and ED visits [ 6 ]. Recent research conducted in 2021 involving 852 intoxicated patients in Najran, Saudi Arabia, revealed that most of the overdose cases were accidental (64.6%) [ 7 ]. Another study in the Western Region of Saudi Arabia found that most cases were in the summertime; moreover, analgesic and non-steroidal anti-inflammatory drugs (NSAIDs) were the most common drugs reported [ 4 ].…”
Section: Introductionmentioning
confidence: 99%